Evaluasi Program Kelompok Usaha Bersama (KUBE) di Kecamatan Batu Kota Batu - Bagus Nugroho Putro; Saiman Saiman; Iradhad Taqwa Sihidi (Department of Public Administration, Muhammadiyah University of Makassar, 2020)
The implementation of the Joint Business Group (KUBE) program in the Batu City Batu District began in 2015 and is still ongoing today. Until now, there are around 21 active KUBE groups in this sub-district and 21 inactive KUBE groups (the most in Kota Batu). This research then aims to evaluate the KUBE program in the sub-district of Batu, Batu City. This research uses a qualitative model with a descriptive type. Data collection techniques through observation, interviews, and documentation. The subjects were interviewed by the Batu City Social Service, KUBE assistants, and KUBE administrators in Batu District. The results of this study indicate that the KUBE program has not been running according to what is targeted by the Batu City Social Service. The effectiveness criteria are still not fulfilled because KUBE members are not actively producing. Likewise, with the efficiency criteria, KUBE members are still confused in managing funds, and the products that are sold sometimes do not run out. The criteria for the adequacy of the results obtained are not sufficient for daily needs. The criteria for equitable distribution of benefits have been felt, but not for the results. The responsiveness criterion is still lack of mentoring and monitoring and evaluation from the mentor. The criteria for the accuracy of the aid distribution process are good and precise, but not many KUBE has carried out independent graduations.Keywords: batu city, joint business group (KUBE), policy evaluation, welfare